2002
DOI: 10.1111/1467-8624.00394
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Novel Objects during Verb Learning

Abstract: Three experiments provided evidence that 3.5- to 4-year-old English-speaking children (N = 72) attend to the appearances of novel objects, not only when they hear a novel noun, but also when they hear a novel verb. Children learning nouns in the context of novel, moving objects attended exclusively to the appearances of objects, even though nouns were also related to the motions of those objects. Children learning verbs attended equally to the appearances of objects and their motions. The latter result contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
126
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(143 citation statements)
references
References 31 publications
13
126
0
4
Order By: Relevance
“…The present findings on noun and verb memory may be related to recent findings by Kersten and Smith (2002) on noun and verb learning. They found that 3.5-to 4-year-old children learning a novel verb attended just as strongly to the appearance of an object as to its motion.…”
Section: Discussionsupporting
confidence: 91%
“…The present findings on noun and verb memory may be related to recent findings by Kersten and Smith (2002) on noun and verb learning. They found that 3.5-to 4-year-old children learning a novel verb attended just as strongly to the appearance of an object as to its motion.…”
Section: Discussionsupporting
confidence: 91%
“…Replicating results from previous studies [104,107,111,112], in the two control conditions with novel words that did not sound-symbolically match their referent actions, both Japanese and English 3-year-olds failed to generalize the newly taught verb to the identical action performed by a different actor. However, when the novel verb sound-symbolically matched the action, not only Japanese 3-year-olds but also Englishreared 3-year-olds (who were not familiar with the sound symbolic system of Japanese mimetics) were able to use this cue to generalize the verb to a new event (see also Yoshida's study [114] for similar findings).…”
Section: (B) Helping Children Find the Invariance For Generalizationsupporting
confidence: 75%
“…Further, in both languages, 3-year-olds were unable to map the verb to the action in either language, performing at chance levels. This finding challenges the assumption that all words are initially interpreted as nouns or objects by young children (see also Echols & Marti, 2004;Kersten & Smith, 2002;Kersten et al, this volume). It also clearly demonstrates that children can map words to objects before they do so for actions.…”
Section: --Insert Figure 1 About Here --mentioning
confidence: 74%